Modeling Household Water Demands Using Sinusoidal Models - Onyoni, Robert Orwenyo; Orwa, George Otieno; Muga, Zablon Maua (International Journal of Statistics and Applied Mathematics, 2019)
Household water in Kenya is used in agricultural activities, industrial activities and other uses. A lot of water is consumed by indoor appliances. The water management strategy affects the household demand for water. The future demand of water in Kenyan towns has remained uncertain. Therefore this study sought to model household water demand using the non- parametric model in the spectral domain. This study largely relied on the secondary data that was collected from Gusii Water and Sanitation Company (GWASCO) situated in Kisii town. This study inspected the data for trend by applying Mann Kendal trend test and it was realized that the p-value = 0.012< Siginificance level, α = 5% indicating that the water demand data had a trend. The parameters of the sinusoidal model was estimated and they were: B1 = 90.28176, B2 = 69.06094 and u = 3586.94540 the developed model was used in conducting in sample forecasting. The forecasted values were plotted together with those of GWASCO and comparison was made. This study noted no significant difference in the plots. Therefore, the model was employed in conducting out of sample forecasting. The out sample forecasted values increased with time. This study concluded that the water data had a trend, had periodic variations hence could be modeled using the sinusoids and that the forecasts increased with time.
Keywords: Trend; spectral domain; non-parametric; sinusoidal model